2022
DOI: 10.1097/mog.0000000000000893
|View full text |Cite
|
Sign up to set email alerts
|

In vitro models to study Clostridioides difficile infection: current systems and future advances

Abstract: Purpose of reviewClostridioides difficile infection (CDI) is the most common cause of healthcare-associated diarrhoea in western countries, being categorized as an urgent healthcare threat. Historically, researchers have relied on the use of in vivo animal models to study CDI pathogenesis; however, differences in physiology and disease prognosis compared with humans limit their suitability to model CDI. In vitro models are increasingly being used as an alternative as they offer excellent process control, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…In general, in vitro models (including MiGut) offer a very useful tool for simulating the GM. However, a criticism of these systems is that they can be over‐simplistic and fail to adequately simulate some of the complexity of the in vivo environment (Ewin et al, 2023 ). For example, it has been shown that there are differences between the sessile and planktonic bacterial communities of the colon, and the ability to sample both groups would give a more complete view of the GM (Bircher et al, 2020 ; Crowther et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…In general, in vitro models (including MiGut) offer a very useful tool for simulating the GM. However, a criticism of these systems is that they can be over‐simplistic and fail to adequately simulate some of the complexity of the in vivo environment (Ewin et al, 2023 ). For example, it has been shown that there are differences between the sessile and planktonic bacterial communities of the colon, and the ability to sample both groups would give a more complete view of the GM (Bircher et al, 2020 ; Crowther et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%